Factores de riesgo biopsicosociales de los estudiantes de rediseño de la carrera de Medicina de la Universidad Nacional de Loja - Méndez Salinas, Karla Jhuliana (2021)
Bio-psychosocial risk facts in students determine their Academic development, so the following investigation is aimed to determine the biological, psychological and social risk factors of the re-designed students of the Medical Career from the National University of Loja, the study had a quantitative, prospective and cross sectional cohort approach, with a sample of 147 students to whom the socioeconomic survey of Institutional University welfare, Beck Test and Hamilton test was applied. The results reveal that in the biological risk factors 69% (n=102) are women of whom 1 was in a gestational state. 63% (n=92) consume alcohol, social drinkers 13% (n=19) tobacco and 3% (n=4) drugs.On average, 81% eat 4 meals a day. Psychological factors 48% (n=17) presented minimal depression within them 30% (n=21) greater anxiety; 57% (n=84) presented greater anxiety of which 94% (n=17 presented moderate depression. Social risk factors 98% (n=144) registered unmarried marital status. 1% (n=2) of students finance their studies, of which 50% (n=1) have a lower income than a basic salary. 48% (n=70) its origin was the city of Loja and 52% (n=77) outside the city. 3% (n=5) of students work. These data show that there are biological, psychological and social risk factors in medical career redesign students and they must receive counseling and guidance therapy. Keywords: Anxiety, Depression, Alcohol and Drugs